Cases in leadership - Rowe, W. Glenn; Guerrero, Laura (Thousand Oaks, California SAGE, 2019)
By connecting theory to practice, this distinctive collection of 30 real-world leadership cases from Ivey Publishing and 15 practitioner readings from the Ivey Business Journal helps students gain a better understanding of leadership and prepares them to be effective leaders today and throughout their future careers. The cases explore integrative issues, such as globalization, diversity, ethical dilemmas, and motivation, giving readers opportunities to confront difficult real-world decisions that have captured the attention of managers in recent years. An invaluable companion to any standard leadership text, this Fifth Edition is fully updated with the most contemporary cases and readings and features a new chapter on followership topics. --Provided by publisher.
Includes bibliographical references.
Keywords: Leadership -- Case studies; Management -- Case studies